Information and Control System of Traverse and its Integration into Cybernetic Centre - Liguš, J.; Zolotová, I.; Karch, P.; Ligušová, J. (Elektronika ir Elektrotechnika, 2010)
This paper deals with the features of hierarchical information and distributed control systems in education and research in general. It presents analysis and realization of local and remote process and supervisory control of specific controlled system - traverse, too. Logical and physical models of architecture were applied for control of real laboratory system and implemented by professional tools. The final controlled and control system was integrated into Cybernetic centre at the Department of cybernetics and artificial intelligence. It contributed to improving of education and research activities of our community.